Understanding the political world a comparative introduction to political science - Danziger, James N. (Pearson, 2013)
Understanding the Political World offers a comparative perspective on how politics works at the global, national, group, and individual level. Focusing on how fundamental concepts in political science relate to real political events, this bestselling text surveys political behavior, systems, and processes throughout the world and asks students to evaluate and apply this knowledge. Through an engaging writing style, numerous examples, and the instructive use of visuals, Understanding the Political World encourages readers to think like political scientists and to critically examine new and enduring political realities and challenges.